Facilitators and Threats to the Patient Dignity in Hospitalized Patients with Heart Diseases: A Qualitative Study - Fariba Borhani; Abbas Abbaszadeh; Roghayeh Mehdipour Rabori (Shiraz University of Medical Sciences, 2016)
Background: Patient's dignity is an important issue which is highlighted in nursing It is an issue that is highly dependent on context and culture. Heart disease is the most common disease in Iran and the world. Identification of facilitator and threatening patient dignity in heart patients is vital. This study aimed to explore facilitator and threatening patient dignity in hospitalized patients with heart disease. Methods: This qualitative content analysis study was performed in 2014 in Kerman, Iran. 20 patients admitted to coronary care units and 5 personnel were selected using purposeful sampling in semi-structured and in depth interviews. Researchers also used documentation and field notes until data saturation. Qualitative data analysis was done constantly and simultaneously with data collection Results: Three central themes emerged: a) Care context which includes human environment and physical environment, b) Holistic safe care including meeting the needs of patients both in the hospital and after discharge, c) Creating a sense of security and an effective relationship between patient and nurse, including a respectful relationship and account the family in health team. Conclusion: The results of this study showed that care context is important for patient dignity as well as physical environment and safe holistic care.